2009
DOI: 10.1136/oem.2008.044917
|View full text |Cite
|
Sign up to set email alerts
|

Organisational justice and markers of inflammation: the Whitehall II study

Abstract: This study suggests that organisational injustice is associated with increased long-term levels of inflammatory markers among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 50 publications
1
51
1
Order By: Relevance
“…These conditions have previously been found to be associated with both cognitive function and organisational justice perception 14 36 41 42. It is also possible that poor physical health status intensifies negative perceptions of environmental stressors or that mild cognitive decline adversely affects justice evaluation by deteriorated work performance.…”
Section: Discussionmentioning
confidence: 98%
“…These conditions have previously been found to be associated with both cognitive function and organisational justice perception 14 36 41 42. It is also possible that poor physical health status intensifies negative perceptions of environmental stressors or that mild cognitive decline adversely affects justice evaluation by deteriorated work performance.…”
Section: Discussionmentioning
confidence: 98%
“…Lower occupational levels may increase the virulence of H. pylori as well as interfere with the immune response to infection through increased energy expenditure or other pathways (Rosenstock et al, 1996). In addition, a recent study found that the inability for employees to make decisions affecting the experience of fairness was associated with increased long-term levels of inflammatory markers CRP and IL-6 among men (Elovainio et al, 2010). A systematic review of psychosocial job stress and immunity found that greater job satisfaction may have a positive impact on immune outcomes and that unemployment and job security are significant factors leading to reduced cellular immune response (Nakata, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In another study based on the Whitehall II Study cohort, a five-item scale for organizational justice was constructed by using items from existing scales that were originally designed to measure effort-reward imbalance and social support [38]. This five-item scale had Cronbach's α coefficients ranging between 0.71 and 0.73 [39][40][41][42]. In studies from Finnish researchers, organizational justice was evaluated with three subscales-distributive justice scale (four items, α=0.62), procedural justice (seven items, α= 0.92) and interpersonal justice (six items, α=0.95) [43].…”
Section: Discussionmentioning
confidence: 99%